How many cards do you use? - Oz Shy (Federal Reserve Bank of Boston, 2013)
This paper investigates how buyers allocate their spending among debit, credit, and prepaid cards. Using the 2012 Diary of Consumer Payment Choice, I show that consumers tend to concentrate the majority of their transactions and a large value of their transactions on a single type of card. The paper also investigates whether buyers concentrate their spending on one of the card networks, a behavior known as "single-homing."
Keywords: D14; 330; payment card use; choice of payment cards; multi-homing; single-homing